Using ACASI to Measure Gender-Based Violence in Ugandan Primary Schools - Punjabi, Maitri; Norman, Julianne; Muyingo, Peter (RTI Press, 2021)
School-related gender-based violence (SRGBV) remains difficult to measure because of high sensitivity and response bias. However, most SRGBV measurement relies on face-to-face (FTF) survey administration, which is susceptible to increased social desirability bias. Widely used in research on sensitive topics, Audio Computer-Assisted Self-Interview (ACASI) allows subjects to respond to pre-recorded questions on a computerized device, providing respondents with privacy and confidentiality. This brief contains the findings from a large-scale study conducted in Uganda in 2019 where primary grade 3 students were randomly selected to complete surveys using either ACASI or FTF administration. The surveys covered school climate, gender attitudes, social-emotional learning, and experiences of SRGBV. Through this study, we find that although most survey responses were comparable between ACASI and FTF groups, the reporting of experiences of sexual violence differed drastically: 43% of students in the FTF group versus 77% of students in the ACASI group reported experiencing sexual violence in the past school term. We also find that factor structures are similar for data collected with ACASI compared with data collected FTF, though there is weaker evidence for construct validity for both administration modes. We conclude that ACASI is a valuable tool in measuring sensitive sub-topics of SRGBV and should be utilized over FTF administration, although further psychometric testing of these surveys is recommended.
Keywords: Audio Computer-Assisted Self-Interview; school-related gender-based violence; gender attitudes